Sebuah Defence and Security System Against The Threat of Drone Weapons In The Oil and Gas Industry As a Vital National Object - Ulul Azmi; Yayat Ruyat; Lutfi Adin Affandi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Ensuring national defense and security is a top priority for every country, particularly when it comes to safeguarding critical infrastructure and strategic resources. Indonesia, being a prominent oil producer in Southeast Asia, is confronted with various threats to its oil and gas sector, including the emerging menace of drone attacks. This research delves into the development of defense strategies through an extensive literature review, shedding light on the potential risks posed to the oil and gas infrastructure. The primary objective of this study is to present recommendations for fortifying defense systems against drone threats targeting national vital assets within the oil and gas industry. The research emphasizes the importance of risk identification, understanding potential impacts, and formulating effective defense strategies. The case analysis of the Saudi Aramco attack serves as a poignant reminder of the critical need to safeguard national vital assets promptly. To tackle this growing challenge, collaboration between the government, relevant institutions, and the private sector becomes imperative. Building an effective and responsive defense system against drone threats in the energy sector necessitates a collective effort. The threat of drone weapons in the oil and gas industry extends beyond mere infrastructure concerns, encompassing potential attacks on facilities and personnel, thereby significantly impacting production and overall security. To strengthen defense mechanisms, the research underscores the importance of leveraging advanced technology, establishing no-fly zones, conducting comprehensive personnel training, implementing stringent regulations, and fostering intelligence information exchange. These measures collectively contribute to a robust defense strategy that can effectively mitigate the risks associated with drone threats in the oil and gas sector. In conclusion, a multifaceted approach that incorporates technological advancements and collaborative efforts is essential to ensure the resilience and security of a nation's vital assets in the face of evolving threats.